CARIS CARIBBEAN DIRECTORY - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
CARIS (The Current Agricultural Research Information System) has recently published a Directory of Current Agricultural Research Projects in the Caribbean. This directory is the first of its kind for the region, and was made possible through...